Instilling Character Values in Early Childhood According to the Qur'an Surah Luqman Verses 12-15 (Study of Tafsir Al-Maraghi and At-Tarbawi) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This research discusses Character Values in the Qur'an Surah Luqman Verses 12-15 (Study of Tafsir Al Maraghi and At Tharbawi). This research is a literature research or literature review, namely research that examines or examines critically, knowledge, ideas, or findings contained in an academically oriented body of literature, and formulates theoretical and methodological contributions to certain topics. In this study the author used the Quran research method. In relation to the discussion in this study, the author quotes the interpretation of the Qur'anic verses through the book Tafsir Al-Maraghi which examines the cultivation of character education values in early childhood. To maximize the discussion of the tafsir study, the author strengthens the content of the thesis writing with the tahlili tafsir method. The results of the analysis show that the values of character education contained in the Qur'an Surah Luqman Verses 12-15 (Study of Tafsir Al Maraghi and At Tharbawi) there are several values, namely: Character of gratitude to Allah, Character of faith in Allah, Character of obedience and filial piety to parents, Character of doing good, character of worship, social character.